(untitled) (Indian Journal of Animal Production and Management, 2025)
Objectives: This study investigates the histological structure of the hypothalamus in wild and albino rats, highlighting significant differences in their cellular composition and organization. Methods: twelves’ healthy rabbits, and all experimental animals have been adapted in the animal house. The current study includes comparative examinations between two types of animals that were divided into two groups: wild and albino rats, (6 animals for each group). The routine stained used (Haematoxylin and Eosin Staining). Results: The hypothalamus of wild rats is composed of many nuclei organized into discrete areas, each of which carries out specific tasks. with the anterior part of the hypothalamus having a greater concentration of nuclei. While glial cells are less common in wild animals, the majority of neurons in wild rats are multipolar, have long axons, and have a rich cellular structure that highlights the hypothalamus. The hypothalamus of albino rats, on the other hand, has larger nuclei, which are clustered in the posterior region. Compared to wild rats, these nuclei have a lower blood supply and are made up of thinner and smaller neurons. These cells’ cellular distribution and arrangement imply that the hypothalamus of albino rats supports a wider variety of functions than that of other species. Important anatomical differences between the hypothalamus of wild and albino rats are further highlighted by the fact that albino rats have a higher number of glial cells, particularly astrocytes, which are scattered and mixed with the neuropil. Conclusion: According to the histological comparative study, the hypothalamus of the two rat species differed greatly, depending on their diets and behaviors.